Socio-digital intervention: Towards what future do we want to walk to? (Sociología y tecnociencia, 2021)
This document pretends to be an approximation as to how digitalization can modify social intervention due to the recent developments of artificial intelligence inspired technologies. The object of study is centered within  the context of social services, and concretely in the figure of Social Work, however, the findings of this study may be carried over to any other discipline that performs its activity in social intervention (SocialPsychology, Social Education, Pedagogy, Sociocultural   work, etc.).We will go through the theoretical perspectives and scientific worldviews that analyze the techno-society relationship, with the aim of framing this study and having interpretative frameworks on the social perception of technology. Moreover, we will analyze what the real impact of digitalization is being in the field of Social Work, based on mixed methodologies that combine techniques quantitative (professional surveys) with qualitative techniques (interviews with key informants from the technology sector and the disciplines of social intervention).In short, the research questions that motivate this work have an exploratory nature: assess what the real penetration of information technologies is; what reception they have had between professionals and citizens; and what perception do professionals have regarding the impact on their professional action. A photograph of the present and a forecast of the possible future scenarios that are drawn for social intervention.
Keywords: social intervention; digitalization; artificial intelligence; social services; social work